Broken Piece of Ceramic Cup Causing Fatal Accidental Cut Throat Injury in a Child: A Rare and Tragic Case Report - Jaydev R Thakre; Harish S. Tatiya; Hemant Vaidya; Vijay T. Jadhav (Indian Journal of Forensic Medicine and Pathology, 2025)
Accidental cut throat injuries are common usually in home or workplace. However, accidental cut throat injuries leading to death have been of rare occurrence in forensic literature. In present case,𿿿ve years old male who was carrying mpty eramic cups, used for serving tea, accidentally slipped, leading to fall of ceramic cups causing its breakage, followed by fall of child over broken pieces of cup causing cut throat injury. He succumbed to death after around 22 hours of incidence, due to aspiration of blood subsequent to cut throat injury. We hereby report the case in view of its rarity in forensic literature, as well as to document the unknown and potentially preventable hazard from ceramic objects in the pediatric population